Developing a NIR emitting benzothiazolium-thioxanthene dye and its application for the design of lysosomes-targeting palladium(II) probe. (December 2021) - Liu, Qiuchen; Li, Ji; Liu, Chang; He, Song; Zhao, Liancheng; Zeng, Xianshun; Wang, Tianhui
Abstract: 'of a near-infrared (NIR) fluorescent probe, ' Palladium ions show many negative effects on human health via the interference with the tissue macromolecules and the function of enzymes. In this paper, a novel benzothiazolium-thioxanthene hemicyanine dye BTX-OH has been synthesized for the design of a near-infrared (NIR) fluorescent probe. The dye BTX-OH in aqueous solution showed its absorption and fluorescence emission maxima in the NIR region at 750 nm and 795 nm, respectively. The application of the dye in designing a Pd 2+ -selective fluorescence probe BTX-A based on a "protect-deprotect" strategy by using an allyl carbonate group as the specific Pd 2+ -responding site has been demonstrated. The probe BTX-A exhibited high selectivity and sensitivity for detecting Pd 2+ ions. In the presence of Pd 2+ ions, the probe showed an enhanced fluorescence response and accumulated specifically in lysosomes in living-cell imaging. Graphical abstract: Image 1 Highlights: A novel benzothiazolium-thioxanthene hemicyanine dye has been prepared. The dye showed absorption and fluorescence maxima in the NIR region. The dye has been applied for the design of Pd 2+ -selective fluorescence probe. The Pd 2+ -selective fluorescence probe is accumulation in lysosomes in living-cell.